Regenerative Green Infrastructure Governance in Weak, Rebounding, and Wealthy Land Markets - Foo, Katherine (Frontiers in Sustainable Cities, 2021)
Too often scholars valorize green infrastructure without critically examining the dynamic and multi-faceted ways that greening impacts urban environments. Cities are complex, evolving forces of their own, which grow and shrink according to time and place. Governance strategies in different economic conditions powerfully shape the impacts of specific green infrastructure installations. They determine the value, quality, quantity, and spatial arrangement of green infrastructure. However, most scholarship focuses on the psychological, social, economic, and environmental benefits of urban greening. Green infrastructure is overwhelmingly studied as apart from historical urban governance trajectories, and it largely fails to consider the role of greening within the process of urban regeneration. This disconnect constitutes a significant gap that constrains understanding of green infrastructure for regenerative cities, and it limits our ability to strategically deploy it in beneficial rather than harmful or irrelevant ways. In this article, I argue that green infrastructure lays fundamentally different roles in poor and wealthy parts of cities, and that these roles change as the overall rank and status of the cities change over time. These changing meanings cause city governments to treat green infrastructure as fundamentally different targets of management. These conclusions are based on an ethnography of the public policy processes surrounding urban greening in three cities with different land markets. In the strong land market, the emphasis is placed firmly on revenue-generating projects, and the major players are private firms in conjunction with city departments. Greening is conceived as a byproduct of large-scale development projects, and rarely apart from them. In the weak land market city, in contrast, the environmental and civic organizations play major roles, and they conceive of green infrastructure apart from development projects. Weak land markets seem to create the possibility for increased political participation of environmental actors and for the installation of green infrastructure for the primary purpose of community health and well-being. However, the increased strength of environmental civic coalitions appears negatively correlated with the city's economic capacity to fund greening projects without support from the business community. These dynamics suggest a counter-cyclical relationship between the political will for urban greening and the investment capacity to pay for it. The analysis of green infrastructure in different land markets demonstrates that green infrastructure is deeply embedded in the historical and geographical legacies of cities.